Changes in social participation between 1 and 2 years following moderate-severe traumatic brain injury - Hart, Tessa; Rabinowitz, Amanda (Frontiers in Rehabilitation Sciences, 2022)
Objective To examine patterns of change in social participation in persons with moderate-severe traumatic brain injury (msTBI) between 1 and 2 years postinjury, and predictors of observed change. Participants 375 participants with msTBI enrolled in a single TBI Model System site. Measures and Methods The dependent variable in a linear regression was a reliable change score for the Social Relations subscale of the Participation Assessment with Recombined Tools-Objective, administered at 1- and 2-year follow-ups. Predictors of change included demographics, injury severity, social and functional status at Year 1, and changes in function and life circumstances between years 1 and 2. Results Social participation status did not change substantially for 34 of the sample, while approximately equal proportions of the remainder improved or declined. The regression model was significant (p < 0.001). Improvement was predicted by private vs. public insurance and decline was predicted by a reduction in the FIM functional outcome measure from year 1 to year 2. Marginal predictors included education (higher levels predicting improvement) and year 1 marital status (single status predicting decline). Conclusions Longitudinal change in social participation in the chronic phase of msTBI deserves further study, with attention to resource limitations and the impact of changes in functional status.